Prematurity and neonatal outcome including congenital malformations after maternal malignancy within six months prior to or during pregnancy. (14th September 2017) - Sabeti Rad, Zahra; Friberg, Britt; Henic, Emir; Rylander, Lars; Ståhl, Olof; Källén, Bengt; Lingman, Göran
Abstract: Introduction: The proportion of women who postpone childbearing is increasing. As malignancy risk increases with age, pregnancy in connection with malignancy will become more common. Material and methods: We compared infants born 1994–2011 to women with a malignancy within six months prior to the last menstrual period or during pregnancy with offspring of women without a previous malignancy. Five national registers were used. Results: A total of 790 women with a malignancy diagnosis from six months prior to the last menstrual period up to delivery were identified. Their 802 infants were compared with 1 742 757 infants of women without a malignancy. A high rate of prematurity was found, especially when the malignancy was diagnosed during the second or third trimesters (33%). Most of these premature births were the result of induced delivery before 35 weeks (91%). The most remarkable finding is the observation that these premature infants had a significantly higher risk for neonatal morbidity than premature infants in the control group with an adjusted odds ratio of 2.67 (95% confidence interval; 1.86–3.84). We found a significantly increased risk of mainly relatively mild malformations among infants of women with a malignancy diagnosis within six months prior to the last menstrual period or during the first trimester with a risk ratio of 1.81 (95% confidence interval; 1.20–2.61). Conclusions: A high incidence of prematurity, mostly due to induced delivery, was found, including an increased risk for neonatal morbidity among these infants. An increased risk for relatively mild malformations was also found.